Ντοκιμαντέρ μικρού μήκους: St. Viniri-Το ιερό δάσος της Αγίας Παρασκευής - (:unkn) unknown (My University, 2020)
Το δάσος της Αγίας Παρασκευής στη Βωβούσα, στο Ανατολικό Ζαγόρι, είναι ένα από τα εναπομείναντα ιερά δάση. Ανέγγιχτο στο χρόνο το διατηρούν οι μύθοι που αποτελούν την προφορική παράδοση του χωριού και μεταφέρονται από γενιά σε γενιά.

The forest of Agia Paraskevi in Vovousa, a mountainous village in Western Greece, is one of the last remaining sacred forests. Untouched by the passage of time, it’s being preserved by the myths that comprise the village’s oral tradition, which in turn passes on from generation to generation.
Short film documentary: St. Viniri-The sacred forest
Keywords: Ντοκιμαντέρ, ιερά δάση, μικρού μήκους; Documentary, sacred forests, short film